Feminine Temporality in Banu Mushtaq's Heart Lamp: Selected Stories - Muhammad Rehan Sabir; Muhammad Rehan; Aryati Prasetyarini (Bulletin of Islamic Research, 2026)
South Asian Muslim women's fiction remains relatively underrepresented in Anglophone literary scholarship, particularly writing produced in Indian regional languages. This article examines Banu Mushtaq’s Heart Lamp: Selected Stories (trans. Deepa Bhasthi, 2025) to analyze how feminine temporality is constructed and negotiated in South Asian Muslim women's everyday lives. Drawing on feminist temporality theory, particularly the work of Kristeva, Freeman, and Sharma, and feminist narratology, the study conducts close readings of selected stories from the collection. The analysis identifies four recurring temporal modes: waiting, bodily time, domestic repetition, and counter-temporal rupture, and examines how these are structured through narrative form. The article argues that Mushtaq's fiction constitutes a counter-temporal literary project that resists the linear time of patriarchal and national modernity by centering embodied, cyclical, and constrained temporalities. The study contributes to feminist literary scholarship on South Asian Muslim women's writing and demonstrates the relevance of feminist temporality frameworks for reading Kannada regional fiction.